2022
DOI: 10.1101/2022.05.03.490556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iron homeostasis governs erythroid phenotype in Polycythemia Vera

Abstract: Polycythemia Vera (PV) is a myeloproliferative neoplasm driven by activating mutations in JAK2 that result in unrestrained erythrocyte production, increasing patients’ hematocrit and hemoglobin concentration, placing them at risk of life-threatening thrombotic events. Our GWAS of 440 PV cases and 403,351 controls utilising UK Biobank data found that SNPs in HFE known to cause hemochromatosis are highly associated with PV diagnosis, linking iron regulation to PV. Analysis of the FinnGen dataset independently co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…1) [45][46][47]. A recent report suggests that ERFE may have a diminished role relative to that of inflammation in regulating hepcidin expression in polycythemia vera patients [48]. In this study, deletion of Erfe in polycythemia vera mice did not alter hepcidin levels or disease severity, resulting in unchanged Hct levels or RBC numbers.…”
Section: Key Pointsmentioning
confidence: 47%
See 1 more Smart Citation
“…1) [45][46][47]. A recent report suggests that ERFE may have a diminished role relative to that of inflammation in regulating hepcidin expression in polycythemia vera patients [48]. In this study, deletion of Erfe in polycythemia vera mice did not alter hepcidin levels or disease severity, resulting in unchanged Hct levels or RBC numbers.…”
Section: Key Pointsmentioning
confidence: 47%
“…The authors further explored the hypothesis that inflammation associated with polycythemia vera leads to hepcidin upregulation. Using a human hepatocyte cell line, HepG2 cells, the authors demonstrated that the increased hepcidin expression was induced by polycythemia vera plasma but not plasma from normal controls and was normalized by blocking IL-6 binding to its receptor [48]. These findings suggest that inflammatory cytokines in polycythemia vera may be crucial to disordered iron utilization.…”
Section: Key Pointsmentioning
confidence: 95%
“…36,41,42 These agents could be successful in disorders of erythropoiesis with preserved maturation profile such as polycythemia vera (PV). [43][44][45][46] Finally, the modulation of iron homeostasis as therapeutic option has been also explored in patients with SCD. [47][48][49][50][51] In SCD, iron restriction decreases HbS synthesis, resulting in reduction of the cellular HbS concentration, which in turn modulates the kinetic of HbS polymerization with a secondary beneficial impact on red cell oxidative stress (Figure 1).…”
Section: Molecules Targeting Iron-homeostasis or Heme Synthesismentioning
confidence: 99%
“…RT-qPCR from liver, spleen and bone marrow samples was performed as previously described. 27 Data is presented as -ΔΔCt or -ΔCt, where ΔCt = Ct target gene -Ct Hprt1 and ΔΔCt = ΔCt sample -mean ΔCt control (ZT0; ZT4 dark fed; CT0 or Bmal1+/+ ZT4) . Primers used for RT-qPCR are in the table below:…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Serum iron and liver and spleen non-heme iron was measured as previously described. 27 Serum sTfR and hepcidin were measured by ELISA (Abcam and Intrinsic Life Sciences, respectively).…”
Section: Analysis Of Iron Parametersmentioning
confidence: 99%